Estudo do funcionamento da mola belleville sob carregamento estático e automatização do projeto via microsoft excel/linguagem VBA - Alkmin, Victor Gabriel [UNESP] (2018)
The purpose of this work is to automate the design project of a Belleville Spring under static load as well as knowing its singularities and applications. The project uses Microsoft Excel/VBA programming language (Visual Basic for Applications) to deliver an easy and friendly design program for students and engineering users. The user is responsible for inserting the initial input data. After inserting it, the program executes a series of algorithms containing each step of the Belleville Spring design project and then verifies if the project is feasible. At the end of the program, a final report containing the spring dimensions and factor of safety is shown on screen. The design program (Microsoft Excel/VBA) and main bibliography of this project were intentionally chosen for engineering students due to familiarity and similarities to what is studied in class by them